The effect of Syphacia muris on nutrient digestibility in laboratory rats - Plachý, V; Litvinec, A; Langrová, I; Horáková, B; Sloup, V; Jankovská, I; Vadlejch, J; Čadková, Z; Borkovcová, M (Laboratory animals, 2016)
This study was carried out to investigate how pinworm infection in rats affects nutrient digestibility in the hosts. Twenty-four male outbred Wistar rats were randomly divided into two groups of 12 rats each. The rats from the first group (GI) were kept in cages with bedding containing pinworm eggs, and the second (control) group (GII) were kept in a separate room in clean, uncontaminated filter-top cages. The animals were put into individual metabolic cages later. Metabolic trials lasted five days and records of animal weight, food ingestion, and faecal weight were taken daily. Based on laboratory analysis of the feed and faecal nutrient content, digestibility values were determined. On day 15 of the experiment, the animals were euthanized. Although Syphacia muris were found in all rats from the GI group, animals exhibited no clinical signs. In our experiment, S. muris infection reduced the overall digestibility of all measured nutrients (P < 0.01). The most significant differences in digestibility were observed in the case of crude fibre and mineral matter (P < 0.01).
Keywords: náhodné rozdělení; stravovací zvyklosti; Animals, Laboratory; Digestion; Animal Nutritional Physiological Phenomena; krysa rodu Rattus; Oxyuroidea; zvířata; laboratory rat; potkani Wistar; laboratorní zvířata; Energy Metabolism; energetický metabolismus; Rats, Wistar; Male; trávení; nutrient; infection; fyziologie výživy zvířat; oxyuriáza; nemoci hlodavců; Rats; Syphacia muris; Animals; digestibility; mužské pohlaví; Feeding Behavior; Oxyuriasis; Random Allocation; Rodent Diseases